Terrorist Financing Risk Assessment Tool : Guidance Manual - World Bank (Washington, DC : World Bank, 2022)
The objective of this Terrorist Financing Risk Assessment Tool is to support World Bank Group (WBG) client countries in the assessment and understanding of their terrorist financing (TF) risks per Financial Action Task Force (FATF) Recommendation. The outputs of this risk assessment are expected to guide user countries in applying a risk-based approach to the design and implementation of their regimes for countering the financing of terrorism (CFT) and improve the effectiveness of their CFT measures at national and sectoral levels. The WBG developed a national money laundering (ML) and TF risk assessment tool in 2012–2015 and has been assisting WBG client countries in using the tool for assessing their ML/TF risks. This tool included a module for the assessment of TF risks. Since then, TF risks and typologies have changed, and the FATF’s attention on TF has increased. In 2019, the FATF issued Terrorist Financing Risk Assessment Guidance, following on from its earlier guidance on national risk assessments. This new TF Risk Assessment Tool intends to incorporate these developments and the lessons learned from the implementation of the previous TF module in a wide range of countries.